Analysis Of Factors Associated With The Occurrence Of Tuberculosis Treatment Dropout In The Work Area Of The Subulussalam City Health Office Year 2023 - Nita Fatmasari Bangun; Ermi Girsang; Rapael Ginting (Eduvest - Journal of Universal Studies, 2024)
Tuberculosis (TB) poses a grave threat to those afflicted, contributing significantly to the global mortality rate. Caused by the infectious bacterium Mycobacterium tuberculosis, TB primarily targets the lungs, with Indonesia ranking second in its prevalence worldwide. This study aims to scrutinize factors associated with TB treatment discontinuation within the Subulussalam City Health Service Work Area in 2023, employing a quantitative, cross-sectional approach. A sample of 203 TB patients under treatment within the area was subjected to logistic regression and multiple logistic regression analyses. Findings revealed a correlation between treatment discontinuation and factors such as inadequate knowledge (p = 0.00; OR = 27.81) and adverse drug reactions (p = 0.02; OR = 13.05). Recommendations include enhancing patient education on TB risks to bolster awareness and deter treatment abandonment, instituting recognition programs within health centers to incentivize treatment completion, and acknowledging the proactive role of healthcare personnel in facilitating patient adherence.